Pengaruh Gaji dan Penghargaan Terhadap Kinerja Guru di Madrasah Aliyah Salafiyah Al-Rahmah Mojorejo Kecamatan Pungging Kabupaten Mojokerto - Siti Jamilah; Muslihun Muslihun (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2024)
This study aims to analyze the impact of salary and recognition on the performance of teachers at Madrasah Aliyah Salafiyah Al-Rahmah Mojorejo, Pungging District, Mojokerto Regency. The background of this research is based on the importance of the role of teachers in the education system and the fact that teacher performance often does not meet the expected standards. This study uses a quantitative approach to test three hypotheses: (1) the impact of salary on teacher performance, (2) the impact of recognition on teacher performance, and (3) the combined impact of salary and recognition on teacher performance. Data were collected through interviews with the madrasah head and other relevant research instruments.The research findings show that: (1) The salary variable has a significant impact on teacher performance (t-statistic 2.917 > t-table 1.761; significance 0.010). (2) The recognition variable has a significant impact on teacher performance (t-statistic 3.820 > t-table 1.761; significance 0.002). (3) Together, the salary and recognition variables have a positive and significant impact on teacher performance, with a coefficient of determination of 58.2%.These findings emphasize the importance of salary and recognition factors in improving teacher performance in the madrasah environment. The results of this study can serve as a basis for policymakers to improve the quality of education through improved teacher performance.